Efek Cycling Pada Endothelial Progenitor Cell (EPC) Terhadap Risiko Cardiovascular Desease Pada Lanjut Usia : Systematic Review - Farida Murtiani; Upik Rahmi; Septian Andriyani; Suci Tuty Putri; Lisna Annisa Fitriana (LPPM Hang Tuah Pekanbaru, 2023)
This systematic review aims to review published articles on the effects of physical activity (PA) cycling on biomarkers of endothelial cell function on the risk of cardiovascular disease. Studies involving angiogenic factors were searched in the Medline and Cochrane libraries. Native human studies over 2 weeks of PA intervention were included. Study quality was assessed according to the GRADE evidence system. Results: five complete articles according to the inclusion criteria. Cycling increases angiogenic, endothelial progenitor cells (EPC) and decreased VEGF. The effect of PA on this factor appears to depend on the type and duration of exercise intervention and patient factors, such as the presence of ischemia. As presented in this review, there is strong evidence that cycling physical activity positively affects endothelial cell function and determines the risk of carciovascular disease.